What makes you win? - The perception of handball specific match situations - Redlich, D.; Fasold, F. (5th EHF Scientific Conference "Handball for Life", 21.-22.11.2019, Cologne, 2021)
We investigated the handball players' perceived influence of permitted fouls and other handball specific events on the expected overall team-success. Although we found a significant influence of permitted fouls, the influence size of permitted fouls can be seen as quit low, compared to other handball specific events. Furthermore, team-handball can be seen as an exception for the positive-negative asymmetry effect.